On a causal force constraint mechanism for approximate velocity tracking wave energy control strategies (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Wave energy control strategies may be broadly divided into two categories. The first category includes optimization-based (OB) control strategies, which provide constrained energy-maximizing solutions by resorting to numerical routines. In contrast, the second category comprises non-optimization-based (!OB) control strategies, which do not rely on numerical routines, and provide a (suboptimal) real-time implementable solution. Although !OB strategies represent an appealing alternative to implementing real-time control of wave energy converters (WECs), none of the existing !OB strategies can efficiently handle force (alternatively torque) constraints to limit the operational space of the control action.Considering the limitations of the current !OB WEC control strategies, this paper addresses the design of a causal force constraint mechanism. Succinctly, by implementing the proposed constraint mechanism, the power take-off (PTO) effort can be kept within specific design thresholds, which has significant implications for maintaining the integrity of the associated WEC and PTO components. The proposed constraint mechanism is formulated for an approximate velocity tracking control structure, and includes an outer reference conditioning loop that modulates the velocity reference as the control effort approaches a design threshold. To exemplify the efficacy of the proposed force constraint mechanism, results are particularized for two !OB controllers for WECs: The Simple and Effective (S&E), and a modified closed-loop version of the LiTe-Con+. Although both of these !OB controllers are capable of handling soft position constraints, as outlined in their original proposals, they do not possess mechanisms for handling force constraints. Therefore, this study emphasises the pivotal importance of the proposed force constraint mechanism, which could serve as a crucial complement towards the real-time implementation of !OB control algorithms for WECs.